Multicentered patient-based evidence of the role of free light chain ratio normalization in multiple myeloma disease relapse - Radocha, Jakub; Pour, Luděk; Pika, Tomáš; Maisnar, Vladimír; Špička, Ivan; Gregora, Evžen; Krejčí, Marta; Minařík, Jiří; Machálková, Kateřina; Straub, Jan; Pavlíček, Petr; Hájek, Roman; et al. (European journal of haematology, 2016)
INTRODUCTION: The normalization of free light chain ratio (FLCr) has been introduced as a marker of stringent complete remission (CR) of multiple myeloma (MM). There is currently a lack of literature assessing the role of FLCr on MM disease progression and remission status. PATIENTS AND METHODS: A multicentered retrospective review of 125 patients with MM in CR and various FLCr values was completed. Parameters of interest included patient demographics, FLCr values, complete remission (CR)/relapse status, and time to progression (TTP). The FLCr values were recorded to provide time-dependent findings on the role of FLCr on progression-free survival and overall survival (OS). RESULTS: The mean follow-up time of 125 patients from five hospitals in the Czech Republic was 31 months. A total of 47.2% of patients relapsed (54 of 125) during the follow-up period. The median TTP of patients with normal FLCr (n = 66) was 54.4 and 40.2 months for patients with abnormal FLCr (n = 59) (P = 0.217). None of the patients reached median overall survival regardless of FLCr values (P = 0.821). In the subgroup of newly diagnosed patients after upfront autologous stem cell transplantation (ASCT), there were 55.6% of patients (35 of 63) with normal FLCr and 44.4% (28 of 64) with abnormal FLCr. A total of 34.9% of patients (22 of 63) relapsed in this subgroup. Within the abnormal FLCr patients, a median TTP was 56.3 months, but no median TTP was reached among the normal FLCr patients (P = 0.746). Median OS in patients with normal (nFLCr) and abnormal FLCr (aFLCr) was not reached (P = 0.787). CONCLUSION: We did not observe any benefit from FLCr normalization in CR in myeloma patients in terms of progression-free survival or overall survival.
Keywords: Immunoglobulin Light Chains; dospělí; Recurrence; Female; biologické markery; Biomarkers; Adult; ženské pohlaví; lehké řetězce imunoglobulinů; lidé; Hematopoietic Stem Cell Transplantation; autologní transplantace; Survival Analysis; transplantace hematopoetických kmenových buněk; Antineoplastic Agents; staging nádorů; protinádorové látky; mnohočetný myelom; recidiva; Aged, 80 and over; následné studie; prognóza; retrospektivní studie; Remission Induction; Follow-Up Studies; Male; progrese nemoci; Aged; indukce remise; Disease Progression; Prognosis; analýza přežití; lidé středního věku; senioři nad 80 let; Multiple Myeloma; senioři; mužské pohlaví; Transplantation, Autologous; Retrospective Studies; Middle Aged; Neoplasm Staging; Humans